Intractable hiccup leading to life-threatening malnutrition: case report - Miaśkiewicz, Kinga; Janiak, Maria; Folwarski, Marcin (Frontiers in Nutrition, 2026)
Intractable hiccups, lasting over a month, can severely impair quality of life and, in rare cases, significantly limit the ability to maintain adequate oral nutritional intake. We report a 63-year-old male with a 5-year history of intractable hiccups, 30 kg weight loss (37%), muscle wasting, and functional decline. Extensive diagnostics found no clear cause, and multiple therapies failed. Severe oral intake difficulties prompted initiation of enteral nutrition via PEG with jejunal extension (PEG-PEJ), resulting in a 15 kg weight gain and functional recovery over 6 months. One year later, during a hiccup relapse, the jejunal tube was dislodged. With gastric access intact, we transitioned to gastric feeding, which was well tolerated despite persistent hiccups. This case underscores that malnutrition may be a significant and underrecognized complication in chronic hiccups, with no established nutritional strategies described. Our experience suggests gastric feeding may be feasible in such patients. Further research is needed to guide management.